Зарубіжний досвід становлення системи місцевого оподаткування - Бачо Роберт; Robert Bacho; Bacsó Róbert; Потокі Габор; Gabor Pataki; Pataki Gábor; Иллар Еріка; Illár Erika (Видавничий дім «Гельветика», 2020)
Резюме. Стаття присвячена дослідженню ролі місцевих податків і зборів у забезпеченні автономії бюджетів органів місцевого самоврядування в зарубіжних країнах. Встановлено, що підвищення ролі місцевих податків та зборів і збільшення їх частки у складі доходів є головним напрямком зміцнення місцевих бюджетів та розширення фінансової автономії відповідних територій. Метою дослідження є дослідження світового досвіду становлення системи місцевого оподаткування та його адаптація в сучасній Україні. Система місцевого оподаткування України має низку недоліків, основним із цих недоліків є те, що місцеві податки і збори недосконало виконують фіскальну функцію – вони по суті не змозі забезпечити стабільні і високі доходи до місцевих бюджетів, у зв’язку з цим і досліджено зарубіжний досвід вирішення даної проблеми. В науковій статті доведено, що більшість країн світу мають досить розгалужену систему місцевого оподаткування із їх значною кількістю і найбільш розповсюдженими є прямі податки, серед яких найбільшу питому вагу мають майнові податки, порівняно із непрямими місцевими податковими платежами. Встановлено, що система місцевих податків і зборів відзначається гнучкістю використовуваних фіскальних інструментів, а це дає змогу адаптувати місцеві способи мобілізації фінансових ресурсів до специфічних потреб територіальних громад з урахуванням особливостей державного адміністративно-територіального устрою при дотриманні загальних принципів національної бюджетно-податкової політики.

Abstract. The article is devoted to the study of the role of local taxes and fees in ensuring the autonomy of local govern- ment budgets in foreign countries. It is found that the increase of the role of local taxes and fees and their share in revenues is the main direction of strengthening local budgets and expanding the financial autonomy of the respective territories. The purpose of the study is to investigate the world experience of local tax system establishment and its adaptation in modern Ukraine. The system of local taxation in Ukraine has a number of shortcomings, the main of which is that local taxes and fees poorly perform the fiscal function – they are essentially unable to provide stable and high revenues to local budgets, and in this regard the foreign experience is studied. The article proves that most countries in the world have a fairly extensive system of local taxation with a significant number of taxes and fees and the most common are direct taxes, among which the largest share have property taxes in comparison with indirect local tax payments. It is established that the system of local taxes and fees is characterized by the flexibility of fiscal instruments, which allows to adapt local methods of financial resources mobilization to the specific needs of local communities, taking into account the peculiarities of state administrative and territorial system in compliance with the general principles of national fiscal policy. Foreign tax systems of local governments are characterized by great diversity, due to both historical reasons (features of regional and local self-government in a given state) and the desire of local authorities to increase the degree of financial autonomy in conditions when the most significant and dynamic tax bases used at the national and local levels are not available. It is proved that in developed countries, local taxes and fees, as a rule, have a fairly large share in the total amount of regional and local governments receipts. Foreign experience in the development of local taxes and fees has been considered. Taking into account foreign experience is important in the modern conditions of Ukraine, due to the need to improve the local tax system as soon as possible in the context of decentralization processes.
Foreign experience in the establishment of the local tax system
Редакційна колегія: http://www.visnyk-econom.uzhnu.uz.ua/index.php/redkolegiya
Зміст: http://www.visnyk-econom.uzhnu.uz.ua/index.php/33-2020
Keywords: місцеві податки і збори; децентралізація; зарубіжний досвід; бюджетно-податкова автономія; інструменти